THE ROLE OF BISEPTOL DRUG IN URINARY TRACT DISEASE - Axmedov Shamshod Jamshidovich (Лучшие интеллектуальные исследования, 2024)
Abstract. Seventy-five patients with prostatic adenoma and sterile urine cultures were treated prophylactically after operation, with one of four antibacterial drugs (Nitrofurantoin, Mandelamine, Biseptol, Chlorocid). Administration of Nitrofurantoin and Mandelamine in the postoperative period was found to be advantageous. In patients receiving these drugs, incidence of urinary tract infections was reduced by one half compared with a control group of untreated patients.